PENGARUH PENGGUNAAN ABU SABUT KELAPA SAWIT SEBAGAI BAHAN PENGGANTI SEBAGIAN SEMEN TERHADAP KUAT TEKAN PAVING BLOCK - firdaus, wahyu; afrizal, yuzuar; gunawan, agustin (Universitas Bengkulu, 2020)
The Oil palm fiber ash has a silica content of 59.1% which make it possible as a partial replacement for cement. This research was aimed to determine the effect of oil palm fiber ash as a partial replacement of cement to compressive strength of paving block. The specimens was made with a size of 20 cm x 10 cm x 6 cm and used a ratio of 1 cement: 3 sand with the variations of the substitution of 0%, 2.5%, 5%, 7.5%, 10%, 12.5% and 15% of the volume cement. The water requirement used the initial flow test according to SNI 03-6882-2002 with each variation had the same amount of water. Specimens printed were soaked in a soaking tub at the age of 1 day for 12 days, then cut into cubes of 5 cm all side using a grinder. The testing of the compressive strength was done at the age of 14 days. Results of the average compressive strength in variations of 0%, 2.5%, 5%, 7.5%, 10%, 12.5%, 15% were respectively 15,13 MPa, 15,36 MPa, 16,02 MPa, 12,97 MPa, 12,16 MPa, 10.00 MPa and 8.01 MPa. The test results showed that the highest increase occurred on the replacement variation of 5% (5.85% from normal paving block) and the maximum decrease occurred on the replacement variation of 15% which was equal to - 47.09% from the normal paving block. The results of the research indicate that the partial replacement of cement with oil palm fiber ash above 5% of the cement volume decreased the compressive strength of paving block. Keywords : oil palm fiber ash, compressive strength, paving block.